Analisis dan Penentuan Prioritas Pencegahan Masalah Menggunakan Failure Mode and Effect Analysis dan Cause and Effect Analysis Pada Proses Bisnis Pengajuan Proposal Program Kreativitas Mahasiswa (PKM) (Studi Kasus : Universitas Brawijaya Malang) - Zaenal Kurniawan; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Universitas Brawijaya (UB) is one of the universities that became an active participant of Student Creativity Program (PKM) organized by Belmawa Dikti. As the most common winner 6 times, UB must improve the quality of competitiveness in order to retain the champion generally back. The steps taken are to submit a proposal of PKM as much as possible with good quality. However, in reality, PKM proposal submission process is not in accordance with the desired target, so that it can hamper the university to reach the target and risk in UB prestative decline. Therefore, it is necessary to do analysis using Failure Mode and Effect Analysis and Cause and Effect Analysis to determine the root and cause of problems that occur. The first step is to identify key business processes for submitting PKM proposals, then modeling business processes using Business Process Model and Notation (BPMN). Next determine the failure that occurs along with the cause and effect that will appear and performed calculations using the Failure Mode and Effect Analysis (FMEA) equation. The next word is to determine the priority failure of some problems based on the highest value. The three highest problems are then analyzed using Cause and Effect Analysis, the purpose is to know the cause and the root of the problem. The result of this research is recommendation of improvement based on cause and root of problem happened at activity or process which have been analyzed.